Understanding transaction costs in the mesoeconomic perspective - Mroczek-Dąbrowska, Katarzyna; Gorynia, Marian (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The aim of this article is to provide an insight into understanding transaction costs on other than the company level. Using the literature review, the foundations of the new institutional economics are evoked to verify whether any obstacles exist that would prevent translating the analysis into the mesoeconomic level. Furthermore, referring to Coase’s suggestion on bonding economics and accounting, a proposal for industry-level operationalisation is presented, based on profit and loss account and highlights different elements of transaction costs. The proposal constitutes a starting point for further meso or macro-economic estimations. It also suggests a more in-depth way of estimating the value of transaction costs in industries and economies that could constitute an alternative for the Wallis and North’s previous estimations of transaction services estimations
Argumenta Oeconomica, 2019, Nr 1 (42), s. 337-360
Keywords: transaction costs; industry; mesoeconomic perspective; new institutional economics